DEVELOPMENT OF MEASURES AND RECOMMENDATIONS TO COMBAT SOIL EROSION IN THE KHOREZM REGION (American Journal of Technology and Applied Sciences, 2026)
This study examines the main causes of soil erosion in the Khorezm region, its negative impact on agricultural lands, and the development of effective measures to combat it. The research analyzes wind and water erosion processes, soil fertility degradation, and deterioration of land reclamation conditions. Furthermore, scientifically based recommendations are proposed, including modern agrotechnical methods, the establishment of protective forest belts, rational use of land resources, and the implementation of innovative technologies. The findings contribute to sustainable agricultural development and environmental stability in the region.